2018
DOI: 10.1111/ger.12322
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporotic alterations in a group of different ethnicity Brazilian postmenopausal women: An observational study

Abstract: Bone density is higher in Brazilian Afro-descendant women than in Caucasians and Asians. Patient's age is associated with bone density and the MCI. The mandibular cortical index is inversely correlated with the peripheral densitometry results within the study ethnic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
2
13
0
5
Order By: Relevance
“…20,21 Maxillofacial area, specially mandible, is proven to be affected by the systemic BMD decrease. 22,23 In this study, a significant correlation was found between the cervical spine and the posterior region of the mandible, as well as a significant correlation between the anterior maxilla and the cervical spine.…”
Section: Discussionsupporting
confidence: 54%
“…20,21 Maxillofacial area, specially mandible, is proven to be affected by the systemic BMD decrease. 22,23 In this study, a significant correlation was found between the cervical spine and the posterior region of the mandible, as well as a significant correlation between the anterior maxilla and the cervical spine.…”
Section: Discussionsupporting
confidence: 54%
“…Although DXA is the golden standard method to evaluate BMD, this examination is not widely available in many countries. In these countries, many imaging tools have been studies to substitute DXA, such as radiomorphometric indexes in panoramic radiographs [8] and the use of examinations performed with different purposes, as Multislice Computed Tomography (CT).…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…The MCI was assessed by evaluating the appearance of the cortical bone at the mandibular endosteal margin on both sides of the mandible, from an anterior limit below the mental foramen to the posterior limit at the mandibular angle, using a previously described classification [10,12]. The mandibular endosteal margin was classified as follows: C1 = normal, when presenting sharp and marked continuous endosteal margin; C2 = moderately eroded, when presenting evidence of lacunar resorption or linear cortical residues; and C3 = severely eroded, when evident porosity was noticed or when presenting persistent and abundant linear bone gaps, reduced thickness, and loss of sharpness of the mandibular endosteal margin.…”
Section: Panoramic Radiographs and MCI Assessmentmentioning
confidence: 99%
“…It is widely used in dental practice and offers excellent visibility of facial anatomical structures. Several studies have applied this examination in assessing mandibular low BMD by analyzing the shape and thickness of the mandibular cortex [9][10][11]. One of the most established techniques is the Klemetti index [12], also known as Mandibular Cortical Index (MCI).…”
Section: Introductionmentioning
confidence: 99%